Why so many children of doctors become doctors : nepotism vs. human capital transfers - Lentz, Bernard F. [Verfasser]; Laband, David N. [Verfasser] (My University, 1989)
"In this paper we document a statistically significant, marginally greater probability of admittance into (at least one) medical school für children of doctors as compared to children of nondoctors. This fact can plausibly be explained as resulting from nepotism, in various forms, as well as from human capital transfers from first to (would-be) second generation doctors. After controlling for acquired human capital und other attributes of medical school applicants, we cannot reject nepotism as a cause - children of doctors are nearly 14 percent more likely to be admitted into medical school than are comparable nonfollowers." (author's abstract) ((en)) In dem Beitrag wird der Frage nachgegangen, warum so viele Arztkinder in den Vereinigten Staaten medizinische Schulen besuchen. Als zwei wesentliche Erklärungsfaktoren werden die Weitergabe von Humankapital zwischen den Generationen oder die Nutzung von Beziehungen herangezogen. (IAB)
Warum soviele Kinder von Ärzten Ärzte werden
Keywords: S 6.4.5.1 Ärzte, Apotheker; Arzt; Berufswahl; Einflussfaktor; Eltern; Berufsproblem; Soziale Beziehungen